THE DIFFICULTIES IN TEACHING VOCABULARY FACED BY THE ENGLISH TEACHERS AT MTs MADANI PAO-PAO MAKASSAR - Ardiyanti S, Sulasri; Kamsinah, Kamsinah; Nurasik, Nurasik; Said, Abdul Muis (English Language Teaching for EFL Learners Journal, 2021)
This research describes the difficulties in teaching vocabulary by the English teachers faced at MTs Madani Pao-Pao Makassar. It is conducted to know the difficulties in teaching vocabulary by the English teacher and also the factors that caused the difficulties in teaching vocabulary at MTs Madani Pao-Pao Makassar. The researcher uses descriptive qualitative to analyse the data. The researcher collects the data through observation and interview. The data are from the interview script. The researcher conducted the data by the English teachers as the subject. The teachers teaching in class 7 at MTs Madani Pao-Pao Makassar. The methods used by the researcher are collecting the data are conducted observation and interviews. The procedure for collecting data analysis is data reduction, data display, conclusion. Based on the class observation and interview, the researcher concludes the difficulties in teaching vocabulary at MTs Madani Pao-Pao Makassar and what are the factors that caused the difficulties for the teachers in teaching vocabulary at MTs Madani Pao-Pao Makassar. Based on the observation and interview, the researcher concluded that the difficulties in teaching vocabulary by the English teacher are classroom management; the teacher’s difficulties in motivating the students; the teaching media is limited (especially textbooks); teacher’s difficulties telling students for memorizing vocabulary. The factors that caused the difficulties in teaching vocabulary are laziness; lack of motivation; lack of vocabulary; students’ lack of pronunciation; and students’ lack of confident when learning English. The researcher suggested for the teachers to learn how to overcome their problems in the English especially vocabulary of the students, classroom management, and motivate the students for learning English because those were the main factors that affect teachers’ difficulties in teaching vocabulary.